2023
DOI: 10.1111/pbi.14016
|View full text |Cite
|
Sign up to set email alerts
|

A natural promoter variation of SlBBX31 confers enhanced cold tolerance during tomato domestication

Abstract: Summary Cold stress affects crop growth and productivity worldwide. Understanding the genetic basis of cold tolerance in germplasms is critical for crop improvement. Plants can coordinate environmental stimuli of light and temperature to regulate cold tolerance. However, it remains unknown which gene in germplasms could have such function. Here, we utilized genome‐wide association study (GWAS) to investigate the cold tolerance of wild and cultivated tomato accessions and discovered that increased cold toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…These studies indicate that BBX proteins are potentially involved in plant cold stress response. Recently, study has identified SlBBX31 as a positive regulator in tomato cold stress response (Zhu et al ., 2023). However, so far, the role and the underlying mechanisms of other SlBBX proteins in cold stress response in tomato plants remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that BBX proteins are potentially involved in plant cold stress response. Recently, study has identified SlBBX31 as a positive regulator in tomato cold stress response (Zhu et al ., 2023). However, so far, the role and the underlying mechanisms of other SlBBX proteins in cold stress response in tomato plants remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…tartaricum ’s high rutin content and self-reproduction [ 81 ]. In addition, a natural promoter variation of SlBBX31 improved cold tolerance during tomato domestication [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, genetic variation in the promoter of a conserved leucine‐rich repeat receptor‐like kinase CTB4a (cold tolerance at booting), confers distinct levels of cold tolerance during temperate japonica evolution in cold habitats (Zhang et al, 2017). In tomato, it was reported that a 27‐bp InDel in the promoter of the CONSTANS‐like transcription factor SlBBX31, is linked to cold tolerance during tomato domestication (Zhu et al, 2023). In our study, all accessions harboring the CsSGR HapG allele were LT tolerant.…”
Section: Discussionmentioning
confidence: 99%